Virtual reality training in laparoscopic surgery / Kee Ming Yit - Kee , Ming Yit (2004)
The second millennium has brought with it a new era of modern surgery. The creation of video surgery is as revolutionary to this century as the development of anesthesia and sterile technique was to the last one. With ten years of solid experience behind them, surgeons can now confidently approach almost every part of the human body with cameras and video monitors. Today more than 90% of all gallbladder surgery is performed laparoscopically, leaving patients with only four tiny marks and minimal discomfort. These dramatic patient benefits make laparoscopic gallbladder surgery the procedure of choice among both surgeons and patients. It is increasingly important for surgeons to practice techniques outside the operating room. These techniques include basic procedural training, allowing for as much repetition as needed, as well as rare critical events. Critical events can be so rare that occasional practice of them is necessary. Currently, a variety of patient simulators allow students to experience life-like medical scenarios m a controlled environment. They provide a medium for instruction in physiology, technical skills, analytical clinical reasoning, and group crisis management. Laparoscopic cholecystectomy (gallbladder surgery) constitutes the basis of all the educational programmes on laparoscopic techniques. This operation and all the other laparoscopic operations begin with the same basic steps. This project will attempt to provide a reasonably realistic virtual reality surgical training environment for a laparoscopic cholecystectomy surgery.